Market Share and Profitability Relationship: A Study of the Banking Sector in Nigeria - Etale, Lyndon M; Bingilar, Paymaster F; Ifurueze, Meshack S (International Journal of Business, Economics and Management, 2016)
This study examined the relationship between market share and profitability of the banking sector in Nigeria. The study involved ten banks listed on the Nigerian Stock Exchange (NSE). Secondary data was collected from the NSE covering a period of nine years from 2003 to 2011. The multiple regression analysis was used to test the hypotheses. The dependent variable in the regression model is profitability represented by profit after tax (PAT), while the independent variables are two components of market share for banks: deposit customers (DC) and loan customers (LC). The results of the study revealed that market share represented here by deposit customers (DC) and loan customers (LC) have positive relationship with profitability (PAT) of the banking sector in Nigeria. The researchers recommended that management of banks in Nigeria should entreat quality of management as an important part of market share effect because superior management causes banks to operate at a higher level of effectiveness and efficiency in managing the deposit portfolio and loan volume which in turn will boost profitability.